TALA’AH AYAT DAN HADIST TENTANG POLIGAMI - Keskarnain, Keskarnain (El-Sirry: Jurnal Hukum Islam dan Sosial, 2023)
The philosophy of Islamic law is knowledge about the essence, secrets, and objectives of Islamic law, both regarding its material and the process of its determination, or the philosophy used to transmit, strengthen, and maintain Islamic law so that it is by the aims and objectives of Allah establishing it on earth, namely to the welfare of humanity as a whole. The aim/use of Islamic Legal Philosophy is to make Islamic law a non-dry source of law for world legislation and provide a basis for legal politics. This means applying Islamic law to achieve its goal, which is closest to the benefit of humanity and avoids damage.